President’s Podium: (Continue to) Be Part of the Solutionl - Adamack, T.L. (Canadian Journal of Optometry, 2026)
... because, as the old adage goes, the alternative is to be a part of the problem. And in all the years of political action by optometrists in Canada, we as professionals can state proudly and unequivocally that we have always been part of, and contributed to, solutions and resolutions in the ongoing challenge of delivering health care to Canadians.